Legal Protection of Business Actors in Digital Trade Agreements: Strengthening Contractual Certainty, Electronic Transaction Security, and Fairness in the Digital Economy Era - Dinda Suciana Rambe; Madina Tuz Zahra Tanjung; Zahwa Khalisa; Rahmat Suryadi Siregar; M. Wahyu Fadillah (ISNU Sumatera Utara, 2026)
The development of digital technology has brought significant changes in the practice of commercial law, particularly in the implementation of trade agreements, which are now often conducted electronically. Digital trade agreements provide convenience and efficiency for business actors, but on the other hand, they also give rise to various legal issues, such as the weak bargaining position of certain business actors, unclear clauses in electronic agreements, and increased potential for disputes due to default and data misuse. Furthermore, the transformation from conventional transactions to digital-based transactions has changed the nature of contractual relationships between business actors. Digital agreements are increasingly formed through electronic platforms, automated systems, and standard contractual mechanisms, which may reduce direct negotiation between parties. This development creates new legal challenges concerning contractual fairness, transparency of electronic clauses, protection of electronic evidence, and accountability of digital platforms involved in commercial transactions. This study aims to analyze the forms of legal protection for business actors in trade agreements in the digital era and assess the effectiveness of applicable laws and regulations in providing legal certainty. The research method used is normative legal research with a statutory regulatory approach, a conceptual approach, and a case approach. The results show that regulations related to trade law and electronic transactions have essentially provided a basis for legal protection for business actors, but there are still obstacles in their implementation, supervision, and enforcement. This research argues that legal protection in digital trade agreements cannot be limited to the recognition of electronic contracts but must also include mechanisms ensuring balanced contractual relationships, protection against unfair standard clauses, and effective dispute resolution mechanisms. Therefore, strengthening digital trade regulation requires an integrated approach between contract law, electronic transaction law, and data protection principles. Therefore, regulatory harmonization, strengthening legal protection mechanisms, and increasing legal literacy for business actors are needed to create a fair, safe, and sustainable digital trade climate.